Makna Maful dan Hikmah Tanggung Jawab Dalam Kehidupan Sehari-Hari - Izzanti, Dina Adzkia; Miranti, Reysha (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Maf'ul in Arabic is the part that receives the action, or in other words, the object of an action. Maf'ul is defined as a reminder that every action will have an impact on others or the surrounding environment, so a person must have a responsible attitude. By understanding the meaning of maf'ul and internalizing the value of responsibility, a person can live a wiser and more meaningful life. The purpose of this paper is to gain a better understanding of the meaning of "maf'ul" in Arabic grammar and the benefits of taking responsibility in everyday life. The method used is a qualitative method with a library research approach. The results of the study indicate that understanding maf'ul can be an important basis for increasing awareness of responsibility that is beneficial in everyday life.